2012
DOI: 10.1002/jbm.a.34428
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent release of growth factors from implant surfaces treated with plasma rich in growth factors

Abstract: Plasma rich in growth factors (PRGFs) technology is an autologous platelet-rich plasma approach that provides a pool of growth factors and cytokines that have been shown to increase tissue regeneration and accelerate dental implant osseointegration. In this framework, the spatiotemporal release of growth factors and the establishment of a provisional fibrin matrix are likely to be key aspects governing the stimulation of the early phases of tissue regeneration around implants. We investigated the kinetics of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 77 publications
(162 reference statements)
1
23
0
1
Order By: Relevance
“…PDGF-BB was released in a more sustained manner during the 7 days of the study; the amount released up to day 7 (1186 pg) was 2.6 times greater than that released during the first 4 h in PBS. This release behavior is in agreement with a recent report by Anitua and coworkers [39] on grade IV titanium discs coated with activated PRP, who found that PDGF was released in a more sustained way than VEGF or TGF-β1. Nevertheless, in our work the release was slightly slower, which is probably because PRP was more tightly embedded onto the PCL nanofibers, compared to the titanium surfaces.…”
Section: Resultssupporting
confidence: 93%
“…PDGF-BB was released in a more sustained manner during the 7 days of the study; the amount released up to day 7 (1186 pg) was 2.6 times greater than that released during the first 4 h in PBS. This release behavior is in agreement with a recent report by Anitua and coworkers [39] on grade IV titanium discs coated with activated PRP, who found that PDGF was released in a more sustained way than VEGF or TGF-β1. Nevertheless, in our work the release was slightly slower, which is probably because PRP was more tightly embedded onto the PCL nanofibers, compared to the titanium surfaces.…”
Section: Resultssupporting
confidence: 93%
“…The versatility of PRF can be broadened when the patient's autologous tissues are transferred along with PRF for grafting or when PRF is used in association with other naturally derived materials, such as gelatin, alginate, collagen or CS, for scaffold modification [241,622626]. PRF combined with additional natural or synthetic materials can yield scaffolds that offer tighter control over their cargo biodistribution and pharmacokinetics [44,605].…”
Section: Formulations Enriched With Endogenous Growth Factorsmentioning
confidence: 99%
“…Furthermore these products do not contain leukocytes and cannot sustain the production of new growth factors after the initial release. On the other hand, the strong fibrin architecture of the L-PRF allows an intense slow release throughout the entire span of the experiment, and the release is further supported by the production of new growth factors by the leukocytes living in the L-PRF membrane (4,11,17,18,21). When L-PRF applied to the implant surface, a protein layer involving massive growth factors are constituted.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy to reduce the osseointegration time has been the modulation of the healing response after the implant placement (2,3). This has been accomplished by biologically active molecules during implant placement to induce osteoconductivity, increase osteoblastic differentiation and enhance healing of peri-implant bone (3,4). Growth factors, bone-specific proteins, bone morphogenetic proteins induce better osseointegration through replication and differentiation of osteoprogenitor cells and interfacial tissue maturation (3-8).…”
Section: Introductionmentioning
confidence: 99%